2017
DOI: 10.3390/md15100325
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Role of Puupehenones in Biomedical Research

Abstract: Marine sponges represent a vast source of metabolites with very interesting potential biomedical applications. Puupehenones are sesquiterpene quinones isolated from sponges of the orders Verongida and Dictyoceratida. This family of chemical compounds is composed of a high number of metabolites, including puupehenone, the most characteristic compound of the family. Chemical synthesis of puupehenone has been reached by different routes, and the special chemical reactivity of this molecule has allowed the synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…In living sponges, these compounds are mainly secondary metabolites, whose natural functions include defense against predators and competition with other sessile species. The increasing interest for sponge-isolated compounds in biomedical and pharmaceutical research derives from the potential clinical applications exhibited by them, according to their antitumoral, anti-inflammatory, antiangiogenic, and/or antimicrobial properties reported [1,2,3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In living sponges, these compounds are mainly secondary metabolites, whose natural functions include defense against predators and competition with other sessile species. The increasing interest for sponge-isolated compounds in biomedical and pharmaceutical research derives from the potential clinical applications exhibited by them, according to their antitumoral, anti-inflammatory, antiangiogenic, and/or antimicrobial properties reported [1,2,3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that PUUP exhibits antifungal activity against the major fungal pathogens C. albicans, Cryptococcus neoformans, and Aspergillus fumigatus (8). In addition to antifungal activity, PUUP also possesses antibacterial, antimalarial, antioxidant, and antitumor activities (9). The exact mechanism by which PUUP exerts these biological activities is not well understood.…”
mentioning
confidence: 99%
“…The exact mechanism by which PUUP exerts these biological activities is not well understood. While one report has shown that the antioxidant activity of PUUP is due to lipoxygenase inhibition, another report indicated that it is due to the inhibition of membrane-bound NADPH oxidases (9). Studies on the antitumor activities of PUUP have suggested that it may target (i) glycogen-synthase kinase-3␤, (ii) matrix metallopeptidase 2, and (iii) hypoxia-inducible factor-2 transcription (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another review article by Martínez-Poveda and colleagues from Spain describes various biological activities of puupehenones (named after the famous rock Puu Pehe in Hawaii)—a large family of chemical compounds initially isolated from sponges of the orders Verongida and Dictyoceratida. This review gives an update on the current knowledge and understanding of the bioactivity and biogenesis of puupehenones, and their possible therapeutic applications in human diseases, with special emphasis on cancer [ 5 ].…”
mentioning
confidence: 99%